(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article explores the psychological and pedagogical foundations of developing lexical knowledge in primary school learners. Based on a comprehensive literature analysis, the study identifies key cognitive, emotional, and instructional factors that influence vocabulary acquisition in young children. The findings underscore the importance of aligning teaching strategies with learners’ cognitive development stages, attention and memory capacities, and emotional engagement. Effective vocabulary instruction requires a balanced approach that combines direct teaching, contextual learning, and interactive activities.